2015
DOI: 10.1016/j.joms.2015.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Postdischarge Nausea and Vomiting Remains Frequent After Le Fort I Osteotomy Despite Implementation of a Multimodal Antiemetic Protocol Effective in Reducing Postoperative Nausea and Vomiting

Abstract: Purpose To assess the prevalence of postdischarge nausea and vomiting (PDNV) after Le Fort I osteotomy with and without the use of a multimodal antiemetic protocol shown to decrease postoperative nausea and vomiting (PONV). Materials and Methods Consecutive patients undergoing Le Fort I osteotomy with or without additional procedures at a single academic institution formed the intervention cohort for an institutional review board–approved prospective clinical trial with a retrospective comparison group. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 53 publications
0
2
1
Order By: Relevance
“…No subjects experienced delayed hospital discharge, remained in the hospital after surgery due to PONV or were admitted after discharge due to delayed PONV (DPONV). The overall and between-group incidence of PONV in this study is lower than the prevalence reported in recent literature for ambulatory surgery ( 49 , 50 ) and specifically for breast surgery ( 35 , 45 , 51 , 52 ). The fact that opioid consumption in our study was comparable between groups most likely did not allow for a significant inter-group difference in PONV.…”
Section: Discussioncontrasting
confidence: 78%
“…No subjects experienced delayed hospital discharge, remained in the hospital after surgery due to PONV or were admitted after discharge due to delayed PONV (DPONV). The overall and between-group incidence of PONV in this study is lower than the prevalence reported in recent literature for ambulatory surgery ( 49 , 50 ) and specifically for breast surgery ( 35 , 45 , 51 , 52 ). The fact that opioid consumption in our study was comparable between groups most likely did not allow for a significant inter-group difference in PONV.…”
Section: Discussioncontrasting
confidence: 78%
“…12 A multicenter cohort study of patients undergoing ambulatory surgery under general anesthesia (GA) in the United States reported 37% of patients experienced postdischarge nausea and vomiting. 13 The estimated costs of PONV in the ambulatory surgical setting can range from $250,000 to $1.5 million in lost surgical revenue. 14,15…”
mentioning
confidence: 99%
“…The incidence of late PONV (POD 2–5 days) was also higher (35%–45%) and the concern of delayed PONV was addressed recently [16,17]. Although there are abundant data on PONV occurrence until 24 h postoperatively, delayed PONV and post-discharge nausea and vomiting after ambulatory surgery deserve further investigation [1820].…”
Section: Discussionmentioning
confidence: 99%